Pentecostal and charismatic education: renewalist education wherever it is found - Kay, William K. (Lexington Books, 2023)
"Pentecostal and Charismatic Education looks at education through the eyes of those who see God at work in the world through the church and beyond. This book offers a worldview invested with traditional Christian theology, but also enlivened by an understanding of the continuing outpouring of the Holy Spirit"--